Orodispersible Membranes from a Modified Coaxial Electrospinning for Fast Dissolution of Diclofenac Sodium - Tingbao Ning (MDPI AG, 2021)
The dissolution of poorly water-soluble drugs has been a longstanding and important issue in pharmaceutics during the past several decades. Nanotechnologies and their products have been broadly investigated for providing novel strategies for resolving this problem. In the present study, a new orodispersible membrane (OM) comprising electrospun nanofibers is developed for the fast dissolution of diclofenac sodium (DS). A modified coaxial electrospinning was implemented for the preparation of membranes, during which an unspinnable solution of sucralose was explored as the sheath working fluid for smoothing the working processes and also adjusting the taste of membranes. SEM and TEM images demonstrated that the OMs were composed of linear nanofibers with core-sheath inner structures. XRD and ATR-FTIR results suggested that DS presented in the OMs in an amorphous state due to the fine compatibility between DS and PVP. In vitro dissolution measurements and simulated artificial tongue experiments verified that the OMs were able to release the loaded DS in a pulsatile manner. The present protocols pave the way for the fast dissolution and fast action of a series of poorly water-soluble active ingredients that are suitable for oral administration.